WHY IS THE GREAT SOLAR ACTIVE REGION 12192 FLARE-RICH BUT CME-POOR? - Sun (孙旭东), Xudong; Bobra, Monica G.; Hoeksema, J. Todd; Liu (刘扬), Yang; Li, Yan; Shen (申成龙), Chenglong; Couvidat, Sebastien; Norton, Aimee A.; Fisher, George H. (Astrophysical journal. Letters, 2015)
ABSTRACT Solar active region (AR) 12192 of 2014 October hosts the largest sunspot group in 24 years. It is the most prolific flaring site of Cycle 24 so far, but surprisingly produced no coronal mass ejection (CME) from the core region during its disk passage. Here, we study the magnetic conditions that prevented eruption and the consequences that ensued. We find AR 12192 to be "big but mild"; its core region exhibits weaker non-potentiality, stronger overlying field, and smaller flare-related field changes compared to two other major flare-CME-productive ARs (11429 and 11158). These differences are present in the intensive-type indices (e.g., means) but generally not the extensive ones (e.g., totals). AR 12192's large amount of magnetic free energy does not translate into CME productivity. The unexpected behavior suggests that AR eruptiveness is limited by some relative measure of magnetic non-potentiality over the restriction of background field, and that confined flares may leave weaker photospheric and coronal imprints compared to their eruptive counterparts.